Buckling analysis of airframe jointed panel under combined loading - Xu Li; Dawei Jia; Chao Meng (Zielona Góra: Uniwersytet Zielonogórski)
The complicated relationship of the high order static indeterminate structure will lead to a lot of calculation work. The strength analysis of the structure is very difficult. In aircraft design phase, a structural simplified method should be used to model the load characteristics of the structure. In the paper, the buckling analysis of airframe jointed panel is investigated under combined loading and the effect of jointed position to buckling load is also presented. For the buckling analysis of special joined structure, one new method which is better than traditional methods is described.
Keywords: strength; buckling analysis; jointed panel; combined loading